How Digital Marketing, AI Integration, Creativity, And Tax Incentives Impact The Profitability Of Micro, Small, And Medium Enterprises - Nailatus Shoffy Rafa Zaelani; Mario Repu Nono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This research aims to investigate how digital marketing strategies, integration of artificial intelligence (AI), creative approaches, and tax incentives influence the profitability of micro, small, and medium enterprises (MSMEs). The study employs a qualitative research model to delve into the intricate dynamics of these factors. Sampling techniques involve purposive selection of MSME owners, managers, and relevant stakeholders. Data analysis is conducted through thematic coding and narrative synthesis to uncover patterns, insights, and implications. The findings illuminate the nuanced interplay between digital marketing strategies, AI utilization, creativity, and tax incentives in shaping the profitability of MSMEs, providing valuable insights for practitioners, policymakers, and researchers.